Appropriate forming conditions for hydroxyapatite-bioactive glass compact scaffold - Wattanutchariya W. (2017)
© 2016, Chulalongkorn University 1. All rights reserved. Biomaterials, such as Hydroxyapatite (HA) and Bioactive glass (BG) have been increasingly implemented in bone substitution due to their biocompatibility and close resemblance to the mineralized phase of human bone. Furthermore, biomaterials can be synthesized from natural sources with calcium-based skeletal structures. In this study, HA and BG were synthesized from bovine bone and mollusk shell, and mixed together to form HA-BG composite biomaterial. Then, the mixtures were compressed into a compact scaffold with dimension of 8×6×8 mm 3 , sintered at 1,000 ˚C for 3 hours and cooled down to room temperature. The compressive strengths of all specimens were evaluated using a universal testing machine. Experimental design was implemented to evaluate the significant factors of forming conditions on the mechanical property of the scaffold. The results revealed that all forming factors have a significant effect on the mechanical property of the composite scaffolds. Consequently, the highest compressive strength (136.92 MPa) was obtained from the scaffold with a 5.85 wt% of BG, 23.41 MPa of pressure and 65.64 seconds of holding time. In addition, Finite Element (FE) modeling was performed to simulate the HA-BG plate under combined loading, and showed that stresses were concentrated near the fracture site and the screw holes.